A Study of metrics for evaluation of Machine translation - Sourabh, K; Aaqib, SM; Mansotra, V (International Journal of Computer Sciences and Engineering, 2025)
Machine Translation has gained popularity over the years and has become one of the promising areas of research in computer science. Due to a consistent growth of internet users across the world information is now more versatile and dynamic available in almost all popular spoken languages throughout the world. From Indian perspective importance of machine translation become very obvious because Hindi is a language that is widely used across India and whole world. Many initiatives have been taken to facilitate Indian users so that information may be accessed in Hindi by converting it from one language to other. In this paper we have studied various available automatic metrics that evaluate the quality of translation correlation with human judgments.